A classification of abdominal lymphatic perfusion patterns after Fontan surgery. (26th February 2022) - Schroeder, Christian; Moosmann, Julia; Cesnjevar, Robert; Purbojo, Ariawan; Rompel, Oliver; Dittrich, Sven
Abstract: OBJECTIVES: Complications after Fontan surgery have been associated with arise and classification of abnormal thoracic lymphatic perfusion pattern. This study compiles abnormal abdominal lymphatic perfusion patterns and investigates their impact on serum protein readings. METHODS: We performed a retrospective analysis of patients who underwent magnetic resonance imaging with T2-weighted lymphatic imaging and serum protein measurements 6 months after having Fontan surgery. The abdominal lymphatic images were classified according to the anatomical lymphatic drainage patterns into 2 categories: (1) para-aortic (types 1–4); (2) portal-venous (types 1–3). Thoracic lymphatic images were classified (types 1–4) as described earlier. RESULTS: A total of 71 patients were included in the study. Para-aortic lymphatic perfusion patterns were classified as type 1 in 4, type 2 in 13, type 3 in 37 and type 4 in16 out of 71 patients. Portal-venous lymphatic perfusion patterns were classified as type 1 in 20, type 2 in 10 and type 3 in 41 patients. Thoracic lymphatic perfusion patterns were classified as type 1 in 8, type 2 in 11, type 3 in 39 and type 4 in 13 patients. The serum protein level was 66 (interquartile range: 7.5) g/l (< standard value in 37%). Higher-grade para-aortic ( p = 0.0062), portal-venous ( p = 0.022) and thoracic ( p = 0.011) lymphatic abnormalities were correlated with lower total serum protein levels. Higher ratings of para-aortic lymphatic abnormalities were significantly associated with higher ratings of portal-venous abnormalities ( p < 0.0001). Ratings of para-aortic and portal-venous classifications were correlated with the thoracic classification ( p < 0.001). CONCLUSIONS: Abnormal abdominal lymphatic perfusion patterns can be classified according to anatomical structures with increasing severity. Higher grade abdominal and thoracic lymphatic perfusion patterns are associated with lower serum protein values. Abstract : The Fontan procedure is a palliative surgical strategy for patients with congenital univentricular heart malformations [1–3].